Kembalikan Lagu Anak-anak Indonesia: Sebuah Analisis Struktur Musik - Ardipal Ardipal Ardipal (LP2M ISBI Bandung, 2015)
ABSTRACTIt appears there are two opposing poles of art music once intertwined within Indonesian society. That is music as art development in certain environments and music as commercial art. In terms of commercial music, almost two decades this song children disappear in the mass media. Was replaced by the song of adults. This certainly influenced the development of psychological, physical, and mental children. Theoretically, this problem this can be seen from the production of music through approach (1) konfik (hegemony) and (2) the interpretation / meaning. This study aimed to compare the musical structure of children's songs and musical structures adults. Data taken from children's songs and pop songs adults. The method of analysis is focused on the features songs based on the structure of the music and effects. Is a key instrument in the researcher's own research and auxiliary instruments in the form of codification guide data. Then describe the elements contained in some of the songs of children and adults. To maintain the validity of the data, performed data triangulation activity. Activity data analysis starts from the stage of selecting and codify the data, analyze the data according to the music features of each, and draw conclusions as well as the verification stage. From the data tracks taken as a sample, it appears that the pattern of rhythmic, melodic, intervals, tempo, tone range is not worthy to be sung by children. Coercion of children to imitate the song can be fatal as damage to the vocal cords, jaw muscle cramps. Finally, it is suggested that participants of art, and also Likewise art network infrastructure, must be able to have the same view and strong in the development of the art of music in Indonesia, especially for a children's song.Keywords: children song, patriotic song, adult song, music structure.ABSTRAKTerlihat ada dua kutub seni musik yang bertentangan sekaligus berjalin di dalam masyarakat Indonesia. Yaitu musik sebagai pengembangan seni di lingkungan tertentu dan musik sebagai seni komersial. Dari sisi musik komersial, hampir dua dekade terakhir ini lagu anak-anak menghilang di media massa. Digantikan oleh lagu orang dewasa. Hal ini tentu mempengaruhi perkembangan psikologis, fisik, dan mental anak-anak. Secara teoritik, masalah ini hal ini dapat ditinjau dari produksi musik melalui pendekatan (1) konfik (hegemoni) dan (2) interpretasi/ makna. Penelitian ini bertujuan untuk membandingkan struktur musik lagu anak-anak dan struktur musik orang dewasa. Data diambil dari lagu anak-anak dan lagu pop orang dewasa. Metoda analisis difokuskan pada fitur lagu berdasarkan struktur musik dan dampaknya. Instrumen kunci dalam penelitian adalah peneliti sendiri dan instrumen pembantu berupa panduan kodifikasi data. Kemudian mendeskripsikan unsur-unsur tersebut yang terdapat dalam beberapa lagu anak-anak dan dewasa. Untuk menjaga keabsahan data, dilakukan kegiatan triangulasi data. Kegiatan analisis data dimulai dari tahap memilih dan mengodifikasi data, menganalisis data sesuai dengan fitur musiknya masing-masing, dan tahap menarik kesimpulan serta verifikasi. Dari data lagu yang diambil sebagai sampel penelitian, terlihat bahwa pola ritmis, melodis, interval, tempo, hingga rentang nada belum laik dinyanyikan oleh anak-anak. Pemaksaan anak-anak untuk meniru lagu tersebut dapat berakibat fatal seperti kerusakan pita suara, kram otot rahang. Akhirnya, disarankan agar partisipan seni , dan juga Demikian juga jaringan infrastuktur seni, harus dapat memiliki pandangan yang sama dan kuat dalam pengembangan seni musik di Indonesia, khususnya untuk lagu anak-anak.Kata Kunci: lagu anak-anak, lagu perjuangan, lagu orang dewasa, struktur musik